Sustainable Materials and Practices in Residential Interior Design - Mansi Gupta; Deepti Pande Rana (International Journal of Solid State Innovations & Research, 2024)
Sustainable materials and practices have emerged as pivotal elements in shaping the ethos of residential interior design. This explores the integration of eco-friendly principles into residential spaces, focusing on materials selection, design strategies, and the broader implications for environmental stewardship. The adoption of sustainable materials encompasses a spectrum of considerations, ranging from renewable resources to recycled materials and low-impact manufacturing processes. This abstract elucidates the significance of materials such as reclaimed wood, bamboo, recycled glass, and natural fibres in reducing environmental footprint while enhancing aesthetic appeal. Moreover, the utilization of non-toxic finishes and adhesives ensures indoor air quality, promoting occupant health and well-being. In addition to material selection, sustainable interior design practices encompass energy-efficient lighting, passive heating and cooling techniques, and water conservation measures. The integration of smart technologies further enhances energy management and reduces resource consumption, thereby fostering a holistic approach to sustainability. Furthermore, the abstract delves into the role of biophilic design in residential interiors, emphasizing the innate human connection with nature. Incorporating elements such as indoor plants, natural light, and organic textures not only enhances visual aesthetics but also fosters psychological well-being and productivity. In conclusion, the transformative potential of sustainable materials and practices in residential interior design. By embracing eco-conscious principles, designers can create spaces that harmonize with nature, promote occupant well-being, and safeguard the planet for future generations.
Keywords: Biophilic Design; Residential Interior; eco-friendly; sustainable materials; transformative potential